KEBERLANJUTAN LINGKUNGAN DAN PEMBERDAYAAN MASYARAKAT MELALUI PENGHIJAUAN DI DESA SENGONKEREP - Fadhilah, Muinah; Riskin Hidayat; Ningrum, Nonik Kusuma; Septyarini, Epsilandri; Hutami, Lusia Tria Hatmanti; Cahya, Agus Dwi; Setiawan, Eko Agus; Larasati, Adelia Ayu; Hidayat, Riskin (Aspirasi Masyarakat, 2025)
The community service program in Sengonkerep Village, Gedangsari District, Gunung Kidul Regency, aims to rehabilitate critical land and empower the community through participatory-based reforestation. The community service team, apart from the Sarjanawiyata Tamansiswa University academic community, also involved foreign campuses: Thepsatri Rajabhat University (TRU) Thailand, Emilio Aguinaldo College (EAC) Philippines and Dong Nai Technology University (DNTU) Vietnam. This activity involves the community in every stage, from preparation, counseling, training, to tree planting. A total of 1,200 trees consisting of sengon (500 trees), jackfruit (100 trees), soursop (100 trees), and munggur (500 trees) were planted in critical areas prone to erosion. This program aims to reduce erosion, improve soil quality, and increase water retention. In addition, the training provided to the community has improved their knowledge and skills in tree planting and maintenance. The evaluation results indicate a significant increase in the community's knowledge regarding reforestation techniques and environmental sustainability. This program has provided positive ecological and socio-economic impacts, with the hope of improving the environmental quality and the community's income in the long term.